Status of Southeast Asia's marine sharks and rays - Naomi Clark‐Shen; Andrew Chin; Sirachai Arunrugstichai; Jessica Labaja; Meira Mizrahi; Benaya Simeon; Neil Hutchinson (Conservation Biology, 2023)
In Southeast Asia, elasmobranchs are particularly threatened. We synthesized knowledge from the peer‐reviewed and gray literature on elasmobranchs in the region, including their fisheries, status, trade, biology, and management. We found that 59% of assessed species are threatened with extinction and 72.5% are in decline; rays were more threatened than sharks. Research and conservation is complicated by the socioeconomic contexts of the countries, geopolitical issues in the South China Sea, and the overcapacity and multispecies nature of fisheries that incidentally capture elasmobranchs. The general paucity of data, funds, personnel, and enforcement hinders management. Reduced capacity in the general fishery sector and marine protected areas of sufficient size (for elasmobranchs and local enforcement capabilities) are among recommendations to strengthen conservation.